Fecal Impaction in the Rectum and Rectosigmoid Colon Secondary to Sunflower Seed Ingestion - Alexander Lyons; Jamie Lee; Kristen Cares (Case Reports in Pediatrics)
A 35-month-old male who had eaten a bag of sunflower seeds initially presented to the emergency department (ED) with visible seeds in the anus and was discharged home with a stool softener after manual disimpaction. He then returned to the hospital 2 days later, and abdominal radiographs confirmed significant fecal material within the rectum and rectosigmoid colon. After failed oral and rectal laxative therapy attempts, subsequent disimpaction under anesthesia revealed an undigested sunflower seed bezoar in the rectum extending to the distal segment of his sigmoid colon. This case highlights the dangers and possible complications of seed ingestion even in small quantities in children along with the pathophysiology of impaction. This is one of the youngest cases reported in the United States involving the rectum and rectosigmoid colon with a sunflower bezoar.